Communication Strategy with Efforts to Improve Cooperation Relationships to Create Effective Productivity in the Manufacturing Industry in Tangerang City - Nia Mintari; Masduki Asbari; Niki Auliya; Taufiq Kimas (Yayasan Aya Sophia Indonesia, 2025)
This study aims to examine effective communication strategies in improving cooperative relationships and creating optimal productivity in the manufacturing industry in Tangerang City. In the era of global competition and technological advancement, effective communication is a crucial factor in building harmonious cooperation between internal and external parties of the company. Through a literature study approach, this study highlights the importance of developing adaptive communication strategies and utilizing mass media and digital technology to overcome communication barriers. The results show that the implementation of appropriate communication strategies can strengthen cooperative relationships, increase workforce engagement, and encourage increased productivity of the manufacturing industry in the area. This study also recommends the need to improve communication competencies for managers and employees and collaboration with related parties for the successful implementation of sustainable communication strategies.